How well do WHO complementary feeding indicators relate to nutritional status of children aged 6–23 months in rural Northern Ghana?. (December 2015) - Saaka, Mahama; Wemakor, Anthony; Abizari, Abdul-Razak; Aryee, Paul
Abstract Background Though the World Health Organization (WHO) recommended Infant and Young Child Feeding (IYCF) indicators have been in use, little is known about their association with child nutritional status. The objective of this study was to explore the relationship between IYCF indicators (timing of complementary feeding, minimum dietary diversity, minimum meal frequency and minimum acceptable diet) and child growth indicators. Methods A community-based cross-sectional survey was carried out in November 2013. The study population comprised mothers/primary caregivers and their children selected using a two-stage cluster sampling procedure. Results Of the 1984 children aged 6–23 months; 58.2 % met the minimum meal frequency, 34.8 % received minimum dietary diversity (≥4 food groups), 27.8 % had received minimum acceptable diet and only 15.7 % received appropriate complementary feeding. With respect to nutritional status, 20.5 %, 11.5 % and 21.1 % of the study population were stunted, wasted and underweight respectively. Multiple logistic regression analysis revealed that compared to children who were introduced to complementary feeding either late or early, children who started complementary feeding at six months of age were 25 % protected from chronic malnutrition (AOR = 0.75, CI = 0.50 - 0.95, P  = 0.02). It was found that children whose mothers attended antenatal care (ANC) at least 4 times were 34 % protected [AOR 0.66; 95 % CI (0.50 - 0.88)] against stunted growth compared to children born to mothers who attended ANC less than 4 times. Children from households with high household wealth index were 51 % protected [AOR 0.49; 95 % CI (0.26 - 0.94)] against chronic malnutrition compared to children from households with low household wealth index. After adjusting for potential confounders, there was a significant positive association between appropriate complementary feeding index and mean WLZ (β = 0.10, p  = 0.005) but was not associated with mean LAZ. Conclusions The WHO IYCF indicators better explain weight-for-length Z-scores than length-for-age Z-scores of young children in rural Northern Ghana. Furthermore, a composite indicator comprising timely introduction of solid, semi-solid or soft foods at 6 months, minimum meal frequency, and minimum dietary diversity better explains weight-for-length Z-scores than each of the single indicators.